Profile of Retinopathy of Prematurity in Infants at a District Hospital in Goa - Menezes Valerie; Naik Saleena; Khemani Chetna; Parsekar Vibha (TNOA Journal of Ophthalmic Science and Research)
Context: Retinopathy of prematurity (ROP) is one of the leading causes of preventable childhood blindness. Aims: To study the profile and risk factors of ROP among infants at a district hospital in Goa. Settings and Design: Retrospective observational study. Materials and Methods: The study included babies screened for ROP at the district hospital from July 2019 to October 2022. The screening was conducted by a single trained ophthalmologist using binocular indirect ophthalmoscopy, and the examination findings along with risk factors were recorded in ROP documentation charts. Statistical Analysis Used: Continuous variables were analyzed using the student t test. Categorical variables were analyzed using the Chi-square test. A P < 0.05 was considered statistically significant. Results: A total of 232 babies were included in the study and were screened for ROP. ROP was detected in 24 babies (10.35%), and 208 babies did not develop ROP. There was a significant relationship between the occurrence of ROP and low gestational age (P < 0.001), lower birth weight (P < 0.001), respiratory distress syndrome (RDS) (P < 0.001), intraventricular haemorrhage (IVH) (P = 0.003), and patent ductus arteriosus (PDA) (P < 0.001). Conclusions: In this study, 10.35% of the babies screened developed ROP. Low gestational age, lower birth weight, RDS, IVH and PDA were significant risk factors for the occurrence of ROP.